Prevalence of Frailty in Older Community‐Dwelling Tanzanians According to Comprehensive Geriatric Assessment. Issue 8 (13th June 2018) - Lewis, Emma G.; Wood, Greta; Howorth, Kate; Shah, Bhavini; Mulligan, Louise; Kissima, John; Dotchin, Catherine; Gray, William; Urasa, Sarah; Walker, Richard
Abstract : Objectives: To investigate the prevalence of frailty using a Comprehensive Geriatric Assessment (CGA) in older community‐dwelling adults living in rural northern Tanzania. Design: Cross‐sectional survey. Setting: Five randomly selected villages in Hai District, Kilimanjaro region, Tanzania. Participants: All adults aged 60 and older living in the selected villages were eligible to participate, including older adults with cognitive impairment provided a close relative was able to assent on their behalf. All participants were community dwelling because institutionalization is very rare. Measurements: Participants were screened using a short frailty screening tool, the Brief Frailty Instrument for Tanzania (B‐FIT), comprising an abbreviated test of cognitive function and the Barthel Index, which assesses functional independence. Based on B‐FIT score, a frailty‐weighted, stratified sample was selected for in‐depth assessment using CGA and characterized as frail or not frail. Results: Two hundred thirty‐six CGAs were performed in 1, 207 people screened, 91 of whom were deemed frail. After adjusting for stratification, the prevalence of frailty was 19.1% (95% confidence interval=15.2–23.1). Conclusion: This is the first study in sub‐Saharan Africa to report the prevalence of frailty in community‐dwelling older adults according to a CGA. The strengths of reporting frailty according to a CGA include the ability to consider likely medical diagnoses based on clinical assessment and to assess individuals' social circumstances and environment.